Formulation and in vitro Evaluation of Verapamil Hydrochloride Floating Tablets: Pharmaceutical sciences- Pharmaceutics - Prajapati, Rima Kumari; P. Muchalambe, Sujatha; Abdul Ahad, Hindustan; Kumar Shukla, Saurabh; Sahani, Pushpa (International Journal of Life Science and Pharma Research, 2023)
The present research work aims to formulate and evaluate novel sustained-discharge floating tablets of verapamilhydrochloride (VPH) which is used for the treatment of hypertension. We aim to use a direct compression technique to formulatethe floating tablets. The characterization of the formulation of VPH was carried out by employing FT-IR and DSC studies, whichshowed that there was no chemical interaction between the drug and polymers, such as HPMC K100M, chitosan, and sodiumalginate. The tablets are designed to have good in-vitro buoyancy, and they remain afloat in the dissolution medium. The bestformulation (F7) is chosen based on its maximum drug discharge (91.91±2.25%) and drug content (97.20±2.71%) over 12h. Thedischarge kinetics of the drug from the tablets are analyzed using various mathematical models, such as zero order, first order,Higuchi, and Korsmeyer's equations. These models help explain and predict drug discharge behavior over time. The studyconcludes that a proper balance between the sustained-release polymer and the gas-forming agent is essential for efficient in-vitrobuoyancy and sustained drug discharge. Formulation F7, which utilized sodium alginate, appears to be the most promising in termsof drug discharge and content.